(untitled) (Indian Journal of Chemistry (IJC), 2024)
Multi-step route toward the synthesis of enantiomerically pure 3-(N-Boc amino) piperidine derivatives is described starting from natural α-amino acid i.e. L-glutamic acid. This route involves the esterification of both carboxylic acid groups in one-pot to give diester followed by NaBH4 reduction to give diol which intern was converted to various piperidines via the reaction of corresponding ditosylate with different amines. The overall yields of substituted piperidine were found to be 44% to 55 % starting from L-glutamic acid.